Design, Expression, and Processing of Epitomized Hepatitis C Virus-Encoded CTL Epitopes - Yerly, Daniel; Heckerman, David; Allen, Todd; Suscovich, Todd J.; Jojic, Nebojsa; Kadie, Carl; Pichler, Werner J.; Cerny, Andreas; Brander, Christian (The Journal of Immunology, 2008)
Hepatitis C virus (HCV) vaccine efficacy may crucially depend on immunogen length and coverage of viral sequence diversity. However, covering a considerable proportion of the circulating viral sequence variants would likely require long immunogens, which for the conserved portions of the viral genome, would contain unnecessarily redundant sequence information. In this study, we present the design and in vitro performance analysis of a novel “epitome” approach that compresses frequent immune targets of the cellular immune response against HCV into a shorter immunogen sequence. Compression of immunological information is achieved by partial overlapping shared sequence motifs between individual epitopes. At the same time, sequence diversity coverage is provided by taking advantage of emerging cross-reactivity patterns among epitope variants so that epitope variants associated with the broadest variant cross-recognition are preferentially included. The processing and presentation analysis of specific epitopes included in such a compressed, in vitro-expressed HCV epitome indicated effective processing of a majority of tested epitopes, although re-presentation of some epitopes may require refined sequence design. Together, the present study establishes the epitome approach as a potential powerful tool for vaccine immunogen design, especially suitable for the induction of cellular immune responses against highly variable pathogens.